The Influence of Nutrient Types and Starter Concentration of Clostridium acetobutylicum in Fermentation of Pineapple Peel into Bioethanol - Silvy Indah Safitri; Sintha Soraya Santi; Sania, Nabilla (Prodi Kimia, 2024)
Bioethanol is an alternative energy source that can be used to reduce dependence on fossil fuels. This study aims to produce bioethanol from pineapple peel waste using Clostridium acetobutylicum bacteria with initial pre-treatment to separate cellulose and lignin. The research methods include raw material preparation, delignification, hydrolysis, and fermentation. The results show that pre-treatment with NaOH solution successfully reduces lignin content in pineapple peels, while hydrolysis using HCl solution increases glucose content. Fermentation with variations in starter concentration and nutrient type resulted in the highest bioethanol content of 4% with the use of urea nutrient and 7% starter concentration. GC-FID analysis indicates that besides ethanol, methanol is also detected as a by-product. In conclusion, Clostridium acetobutylicum bacteria can be used to produce bioethanol from pineapple peel waste, with the concentration of starter and nutrient type influencing the ethanol content produced.